Killed oral cholera vaccines: history, development and implementation challenges. (September 2014) - Lopez, Anna Lena; Gonzales, Maria Liza Antoinette; Aldaba, Josephine G.; Nair, G. Balakrish
Cholera is still a major global health problem, affecting mainly people living in unsanitary conditions and who are at risk for outbreaks of cholera. During the past decade, outbreaks are increasingly reported from more countries. From the early killed oral cholera vaccine, rapid improvements in vaccine development occurred as a result of a better understanding of the epidemiology of the disease, pathogenesis of cholera infection and immunity. The newer-generation oral killed cholera vaccines have been shown to be safe and effective in field trials conducted in cholera endemic areas. Likewise, they have been shown to be protective when used during outbreak settings. Aside from providing direct protection to vaccinated individuals, recent studies have demonstrated that these killed oral vaccines also confer indirect protection through herd immunity. Although new-generation oral cholera vaccines should not be considered in isolation from other preventive approaches in countries where they are most needed, especially improved water quality and sanitation, these vaccines serve as immediately available public health tools for preventing further morbidity and mortality from cholera. However, despite its availability for more than two decades, use of these vaccines has not been optimized. Although there are limitations of the currently available oral cholera vaccines, recent data show that the vaccines are safe, feasible to use even in difficult circumstances and able to provide protection in various settings. Clear identification of the areas and target population groups who will benefit from the use of the cholera vaccines will be required and strategies to facilitate accessibility and usage of these vaccines in these areas and population groups will need to be developed.